Risk Profile, Good Corporate Governance, Earning, dan Capital dalam Memprediksi Financial Distress pada Bank Umum Syariah di Indonesia - Tri Lestari, Hesti; Setiawan, Setiawan; Afiyanti Tripuspitorini, Fifi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
Islamic banks have an important role in every country including Indonesia. The bank aims to maintain economic growth and stability in national finance. This study analyzes and measures the application and capability of the RGEC (Risk, GCG, Earning, Capital) Method in a risk-based Bank Rating (RBBR) approach in predicting financial distress in Sharia Commercial Banks in Indonesia for the 2014-2017 period. Variables studied were Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) , Good Corporate Governance (GCG), Return On Assets (ROA), and Capital Adequacy Ratio (CAR). The results of the study indicate that the RGEC method can be applied and is able to predict financial distress in Islamic commercial banks with Dicriminant Analysis and the accuracy of classification using the Press’Q Statistic.